Investasi Harta Wakaf Melalui Pendekatan Interpretive Structural Model (ISM) - Rozaq, Mahfudz; Rahmad, Dedy (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Investment of waqf property is a potential that should be considered based on the needs and current economic conditions. As explained earlier, it is not only aimed at safeguarding the perpetuity of the property, but also aims to optimally benefit the waqf property for the needs of the community and generate the economic development of the community, especially the Muslim community. Waqf institutions or nazirs at the beginning of the success of Islamic civilization have made various efforts in developing it. Although the business has shown success in the past, it still requires development methods that are in line with sharia principles and current economic conditions. In addition, the Indonesian government has established the waqf act number 41 of 2004. The waqf act aims to increase the potential of waqf to increase the economic development of Muslims. For example, in the waqf act section 16 it is mentioned that waqf property consists of immovable property and movable property. Among movable property are money waqf, securities waqf, intellectual property rights waqf, and others. Although in reality the potential of waqf has not been fully realized, due to the fact that it has not been understood accurately because it is only known for immovable property such as land or buildings, and investing waqf property is still considered a new thing when in fact it has been practiced for a long time.